Wharton-SMU Research Centre Agreement (Institutional Knowledge at Singapore Management University, 1999)
Signing ceremony held on 10 June 1999 at the Ritz-Carlton Hotel to establish the Wharton-Singapore Management University Research Centre. Left to right: SMU Chairman Ho Kwon Ping, Deputy Prime Minister Tony Tan, Minister for Education Teo Chee Hean and SMU President-Designate Janice Bellace. The joint research centre will focus on international business issues relevant to Singapore and Asia, and help establish a research culture at SMU. Professor Janice Bellace is named as the centre director.